Transglutaminase 2 Induces Deficits in Social Behavior in Mice - Amanda Crider; Talisha Davis; Anthony O. Ahmed; Lin Mei; Anilkumar Pillai (Neural Plasticity)
Impairments in social behavior are highly implicated in many neuropsychiatric disorders. Recent studies indicate a role for endoplasmic reticulum (ER) stress in altering social behavior, but the underlying mechanism is not known. In the present study, we examined the role of transglutaminase 2 (TG2), a calcium-dependent enzyme known to be induced following ER stress, in social behavior in mice. ER stress induced by tunicamycin administration increased TG2 protein levels in the mouse prefrontal cortex (PFC). PFC-specific inhibition of TG2 attenuated ER stress-induced deficits in social behavior. Conversely, overexpression of TG2 in the PFC resulted in social behavior impairments in mice. In addition, systemic administration of cysteamine, a TG2 inhibitor, attenuated social behavior deficits. Our preliminary findings using postmortem human brain samples found increases in TG2 mRNA and protein levels in the middle frontal gyrus of subjects with autism spectrum disorder. These findings in mice and human postmortem brain samples identify changes in TG2 activity in the possible dysregulation of social behavior.